SOSIALISASI STRATEGI PEMANFAATAN WEB CANVA PEMASARAN DALAM MEMBANTU KINERJA TIM KADER PENGGERAK PKK KELURAHAN MERUYA UTARA - Riri Fajriah (Universitas Mercu Buana, 2023)
Web Canva technology as a marketing tool is expected to help the PKK Movement Team draw up exciting and professional marketing materials. Socialization is carried out through interactive training, group discussion, and the creation of examples of marketing materials using Canva. Expected with this socialization and learning, the performance of the PKK Movement Team can be enhanced in achieving more effective and efficient marketing goals. Other benefits obtained from the results of socialization and training Web Canva to the PKK Team of The Northern Meruya are to help design the making of logos, posters, packaging design, to promo discount products, media video design digital-based learning as well as make presentation slides more interesting and interactive to give an explanation for the PKK team cadres about the performance realization of the already running PKK Team that can be presented more interesting through the digital template. The final result of the implementation of this PkM activity is the presence of digital transformation and the use of the internet in a healthy way in improving the quality of IPTEK-conscious society in the Meruya Northern Environment. In addition, the activities of dedication to the community are expected to provide significant benefits for the Northern Meruya Foundation, in particular for the PKK Movement Team in optimizing marketing strategies through the use of Web Canva technology. In addition, it is also expected to be an inspiration and example for other regions in increasing the use of information technology in the development of marketing for society.